PROSES PENGOLAHAN KOPI ROBUSTA POROT TEMANGGUNG UNTUK MENGATASI KENDALA CUACA - Rulinawaty Rulinawaty; Andriyansah Andriyansah; Zulham Adamy; Septiyani Endang Yunitasari; Analisa Svastika Ning Gusti Djajasasmita (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
It is important for the global coffee industry to make robusta coffee safely and on time. In this study, we look at how well a simple simulation-based method works and try to guess how much robusta coffee will grow in the Tuanggung area. The main process is the growth and development of coffee, which simulates its response to climate variations and potential water requirements during the foggy growing process. Such weather conditions make Robusta coffee unique in taste. This model was made and tested for people in Indonesia, especially in West Java, which has many coffee farms. The model building is very important for long-term coffee productivity studies in areas where the climate changes drastically and does not have long-term climate stations. This simple process-based model from research on community service (PkM) can be used as a starting point for making robusta coffee with a season that works with a weather forecasting system. This process will help farmers and businesses better prepare and manage their supply chains. For extreme weather changes and increased profitability.